IMMUNE-RELATED GENE EXPRESSION ENHANCEMENT THROUGH THE USE OF SYNBIOTIC FEED IN WHITE SHRIMP CULTURES LITOPENAEUS VANNAMEI IN CLOSED AQUACULTURE SYSTEM RECIRCULATING AQUACULTURE SYSTEMS (RAS) - Janatul Khulud, Liza
The production of white shrimp (Litopenaeus vanamei) supplies 75% of the total production of crops in Southeast Asia. No less than 353,000 tons of white shrimp are produced in Indonesia and are expected to continue to increase. The occurrence of diseases during the production process becomes an obstacle that can reduce the biomass and shrinkage of shrimp during harvest, one of which is the Acute Hepatopancreatic Necrosis Disease (AHPND) caused by the bacteria Vibrio spp., including Vibrio parahaemolyticus. The objective of this study was to determine the modulation of the synbiotic action consisting of prebiotics Kapppaphycus alvarezii (0,375%), Spirulina sp. (0,125%), combined with the probiotic Halomonas alkaliphila (109 CFU/kg of feed; ‘synbiotic H’) or B. cereus (108 CFU / kg of food; ‘sinbiotic B’) to enhance growth and biomass, as well as improve the system of white shrimp's immune response to disease infection by V. parahaemolyticus using gene expression analysis approaches. (transkriptomik). The shrimp was kept in a closed breeding system Recirculating Aquaculture System (RAS) for 149 days, then tested for V. parahaemolyticus and observed for 72 hours. Genetic expression analysis was performed on the intestines of white shrimps using the Quantitative Real Time PCR (qPCR). The results of the trial treatment with V. parahaemolyticus yielded more optimum lifespan results on the H (67.00 ± 7.22%) and B (63.00 12.50%) synbiotic treatments significantly compared to the control treatments (21.00 ? 7.22%). The data from gene expression analysis showed that the administration of synbiotic B feeding can significantly enhance the expression of genes related to immune alf-A and proPO compared to synbiotics H and control treatments. In the relative expression for lectin genes, Synbiotic H treatment has a higher and significant improvement compared with Synbiotics B treatment as well as control treatment. Symbiotic feeding treatment with B. cereus has higher relative expression values compared to H. alkaliphila although there are no real differences. In general, these studies show that the treatment of synbiotic feeding with both B. cereus and H. alkaliphila in closed RAS systems is capable of optimizing growth, providing enhanced expression of immune-related genes, i.e. alf-A, pro-PO, lectin and lysozyme, and improving the survival of white shrimp after the attack of pathogenic bacteria V. parahaemolyticus.